THE EVOLUTION OF THE STRUCTURE BY AGE GROUPS AND THE AGEING OF THE POPULATION IN ROMANIA BETWEEN 1992-2021 - Ionel MUNTELE (Analele Universităţii din Oradea: Seria Geografie)
The ageing of the population has become a problem of maximum interest, in the context of the completion of the demographic transition, especially in European states. Romania, like all of Eastern Europe, is facing the acceleration of this process, against the background of a strong demographic decline after 1990, generated by the drastic decrease in fertility and the massive migration of labor force abroad. The present study proposes a diachronic analysis of the evolution of the age group structure and, implicitly, of the ageing process, based on the four censuses carried out after 1990. The main objective is to detect territorial disparities, on various levels, with the hypothesis of the differentiated action of of factors that can stimulate or inhibit demographic aging. The double analysis (descriptive, respectively factorial) highlighted a series of regional models of evolution that express various ways of adapting to the socio-economic and political transition. The faster expansion of the process studied in cities is an observation that can be the basis of specific studies. On the other hand, the relative rejuvenation of the population in the metropolitan areas expresses a population transfer generated by the change in lifestyle, the relocation of economic activities and the increase in mobility. At the same time, the isolation, the predominance of agricultural activities and the decline in the exploitation of some resources constitute the motive of an ageing without precedent, illustrating certain trends of depopulation of vast areas.